Stream of consciousness in Virginia Woolf’s novels – *Mrs Dalloway* as a model - zernadji, chahira; dendouga, fouzia (El Omda in Linguistics and Discourse Analysis, 2025)
Virginia Woolf suppressed the pain and lived in silence, but she was able to draw her soul with extreme accuracy in the sum of her novels, as she came to the soul, recounting it, and conversing with her in hybrid groups of psychology, philosophies and ideas, due to the collapse of her consciousness and unconsciousness, so she recounted the facts through her suffering and defeated characters. This study came to search for the features of the stream of consciousness in the writings of the suffering novelist, through the novel (Mrs. Dalloway), which is a model for reincarnation of the tense psychological state, and retreat into the corners of the soul and the unconscious.